Recent Advances in Robot Manipulators - Küçük, Serdar (IntechOpen, 2022)
The Industrial Revolution introduced machines to humankind. In the 20th century, robots, which were produced only as toys before, began to be used for business applications. This robotic technology, which has spread to the world in a short time, is now being used in a variety of areas, from cargo transportation to car painting, from electronic card production to material selection, and from surgery to rehabilitation. This book explores the fantastic world of robotics, including current technology and applications as well as the latest advancements.